Adaptação de modelos baseados em splats para superfícies e arestas curvas - Ivo, Rafael Fernandes (2020)
Surface splatting has been proven to be a good approach to render point-based models. Aliasing artifacts are effectively avoided by filtering. Renderings with high performance are achieved by GPU implementations and high quality shadings by normal fields. However, splats are disks in object space and cannot represent properly sharp features, as edges and corners. Besides, when the model is observed in a close-up view or when the model is low sampled, geometric artifacts become visible, such as bumps on silhouette. We present a new method for clipping splats in models with sharp features. Each splat near an edge is an ellipse clipped against a bidimensional rational Bézier curve. We designed and implemented an automatic computation of the clipping curves and an improvement on sampling methods near sharp features. We also present quadric splat, a rendering primitive that improves the rendering of model silhouettes and sharp features, and an algorithm to compute the silhouette set of a quadric splats cloud. Previous methods extract point set silhouettes by thresholding point normal, which can lead to simultaneous over and under-detection of silhouettes. Other methods use neighboring and variational info for this purpose. The quadric splat and the clipping curve are defined by simple and uniform data, thus, our rendering primitives can be implemented completely based on vertex and fragment shaders of current GPUs.